New insights on the structure of the picloram-montmorillonite surface complexes - Marco Brown, José Luis (2015)
Hypothesis: The environmental mobility and bioavailability of Picloram (PCM) are determined by the amine and carboxylate chemical groups interaction with the soils mineral phases. Clay particles, such as montmorillonite (Mt), and the pH value of the media could play an important role in adsorption processes. Thus, the study of the role of soil components other than organic matter deserves further investigation for a more accurate assessment of the risk of groundwater contamination. Experiments: Samples with PCM adsorbed on Mt dispersions were prepared at pH 3-9. Subsequently, the dispersions were separated, washed, centrifuged and stored at room temperature. Picloram (PCM) herbicide interaction with surface groups of montmorillonite (Mt) was studied using XRD, DTA, FTIR and XPS techniques. Findings: The entrance of PCM into the Mt basal space, in two different arrangements, perpendicular and planar, is proposed and the final arrangement depends on PCM concentration. The interaction of PCM with Mt surface sites through the nitrogen of the pyridine ring and carboxylic group of PCM, forming bidentate and bridge inner-sphere complexes was confirmed by FTIR and XPS analysis. The acidity constant of the PCM adsorbed on the Mt surface was calculated.